The moving pictures. Brod, Kafka, Brentano and... Arbus (Materiali di Estetica. Terza serie, 2017)
This paper consists of five sections: (1) introduction; (2) a section about Max Brod’s theory of beauty and Kafka’s critical reply to it, and the account of his philosophical inspirations as well as the story of Brod’s and Kafka’s affiliation to the Louvre Circle; (3) a section on Kafka’s “The Metamorphosis” and the role novelty plays in this story supplemented with an ethical context taken from Brentano; (4) a section in which I analyse this story both as a horror and comedy, and where I introduce a very Kafkaesque photographer – Diane Arbus; finally, (5) a section about the relationship between Kafka and Brod which also serves as closing remarks and summing-up.The research was financed from the assets awarded by The National Science Centre in Kraków for the postdoctoral internship upon the decision no. DEC-2013/08/S/HS1/00184/2.Keywords: Franz Kafka; Max Brod; Franz Brentano; Diane Arbus; Metamorphosis; America; prose; aesthetics; Vorstellung; intentionality; biography; photography; beauty; aesthetics; novelty; Gregor Samsa; Karl Rossmann; metaphor; feeling; emotion; judgment; presentation; evidence; inheritance